Diversion of flashy floods for agricultural use and its effect on nutrition in Ethiopia - Hagos, Fitsum; Mulugeta, A.; Erkossa, Teklu; Lefore, Nicole; Langan, Simon J. (2014)
The study examined whether access to spate irrigation leads to better nutrition outcomes. The results showed that there is an overall improvement in the study sites compared to the 2011 DHS study. As far as households with access to spate irrigation are concerned, weight-for-height z-scores indicated that 8.2% of the children had prevalence of global acute malnutrition; 8.2% of them had moderate acute malnutrition. None of the children had severe acute malnutrition. The weight-for-age results indicated that 27.5, 17.6 and 9.8% of the children showed prevalence of underweight, moderate underweight and severe underweight, respectively. The height-for-age z-scores showed 56.5, 30.8 and 21.7% of the children had prevalence of stunting, moderate stunting and severe stunting, respectively. On the other hand, households without access to spate irrigation indicated that as far as the weight-for-height z-scores of children are concerned, there were no children (boys and girls) with prevalence of global acute malnutrition; weight for-age z-score showed that 13.6, 10.2 and 3.4% of the children had prevalence of underweight, moderate underweight and severe underweight, respectively. The height-for-age z-scores showed that 45.5, 25.5 and 20.0% of the children had prevalence of stunting, moderate stunting and severe stunting, respectively. The anthropometric measures, thus, showed the nutritional outcomes of users were worse-off than of nonusers of spate irrigation. This happens in the face of better income and consumption expenditures, mainly nonfood, for users compared to nonusers. This underlines the importance of nutrition education alongside efforts to improve access to irrigation. Moreover, multisectoral collaborations are needed between the health, agriculture, water, social protection, education, gender and other sectors to improve the nutrition outcome of children.